TINGKAT PEMENUHAN INFORMASI MITIGASI PENANGGULANGAN BENCANA MELALUI ILM PADA LPP TVRI BALI - MULIARTA, I NENGAH (Jurnal Ilmiah Widya Sosiopolitika; Vol 3 No 1 (2021): MEDIA, POLITIK, DAN PANDEMI, 2021)
ABSTRACT TVRI is a public broadcasting institution that in its broadcasting process uses public frequencies and its operations use public funds through budget allocations from the government. As a public broadcasting institution, TVRI has an obligation to provide education and information to the public. This obligation, one of which can be done through broadcasts that are carried out in the form of public service advertisements (PSA). This study aims to determine the level of fulfillment of the spread of disaster mitigation through PSA carried out by TVRI Bali, so that future plans can be made to maximize the spread of disaster mitigation through PSA. The research was conducted by taking data from the TVRI Bali program during October to December 2018. The results showed that TVRI Bali had not fulfilled information related to disaster mitigation, as evidenced by the absence of public service advertisements produced and broadcast related to disaster mitigation. In general, TVRI Bali has not met the minimum percentage of PSA broadcasting compliance in accordance with the Broadcasting Law, Broadcasting Behavior Guidelines (BBG) and Broadcast Program Standards (BPS). Keywords : Mitigation, Disaster Management, PSA, Broadcasting Institutions, TVRI